The Application of fiber optic sensors using Machine Learning algorithms for temperature measurement of lithium-ion batteries - Cierpiak, Kacper; Szczerska, Marta; Wierzba, Pawel (Photonics Letters of Poland, 2023)
Optical fiber sensors using low-coherence interferometry require processing of the output spectrum or interferogram to determine the instantaneous value of the measured quantity, such as temperature, quickly and accurately. Methods based on machine learning are a good candidate for this application. The application of four such methods in an optical fiber sensor of temperature is demonstrated. Using a ZnO-coated sensing interferometer and spectral detection, the sensor is intended for monitoring lithium-ion rechargeable batteries. While the performance of all methods was good, some of them seem to be better suited for this application. Full Text: PDF References B. Wrålsen et al., "Circular business models for lithium-ion batteries - Stakeholders, barriers, and drivers", J. Clean. Prod. 317, 128393 (2021), CrossRef T. Deng et al., "Measuring smartphone usage and task switching with log tracking and self-reports", Mobile Media & Communication 7, 3 (2019), CrossRef Smartphone Subscriptions Worldwide 2027. Statista, DirectLink T. Jerzyński, G. V. Stimson, H. Shapiro, G. Król., "Estimation of the global number of e-cigarette users in 2020", Harm Reduct. J. 18, 109 (2021). CrossRef Battery chemistries, DirectLink Y. Chen, et al., "A review of lithium-ion battery safety concerns: The issues, strategies, and testing standards", J. Energy Chem 59, 83 (2021), CrossRef T. Görgülü, M. Torun, A. Olgun, "A cause of severe thigh injury: Battery explosion", Ann. Med. Surg. 5, 49 (2016) CrossRef T. Maraqa et al., "Too Hot for Your Pocket! Burns From E-Cigarette Lithium Battery Explosions: A Case Series", J. Burn Care Res. 39, 1043 (2018). CrossRef Y. Chen et al., "A review of lithium-ion battery safety concerns: The issues, strategies, and testing standards", J. Energy Chem. 59, 83 (2021), CrossRef Q. Wang et al., "Thermal runaway caused fire and explosion of lithium ion battery", J. Power Sources 208, 210 (2012), CrossRef P. V. Chombo, L. Yossapong, "A review of safety strategies of a Li-ion battery", J. Power Sources 478, 228649 (2020), CrossRef P. Listewnik, M. Bechelany, J. B. Jasinski, M. Szczerska, "ZnO ALD-Coated Microsphere-Based Sensors for Temperature Measurements", Sensors 20, 4689 (2020), CrossRef M. Szczerska, "Temperature Sensors Based on Polymer Fiber Optic Interferometer", Chemosensors 10, 228 (2022), CrossRef M. Kruczkowski et al., "redictions of cervical cancer identification by photonic method combined with machine learning", Sci. Rep. 12, 3762 (2022), CrossRef